2004
DOI: 10.1021/ja0485053
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Simulations and g-Tensor Calculations of Aqueous Benzosemiquinone Radical Anion:  Effects of Regular and “T-Stacked” Hydrogen Bonds

Abstract: Car-Parrinello molecular dynamics (CP-MD) simulations of the benzosemiquinone radical anion in aqueous solution have been performed at ambient conditions. Analysis of the trajectory shows not only extensive hydrogen bonding to the carbonyl oxygen atoms (ca. 4-5.6 water molecules depending on distance criteria), but also relatively long-lived "T-stacked" hydrogen bonds to the semiquinone pi-system. These results are discussed in the context of recent findings on semiquinone-protein interactions in photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 43 publications
(127 reference statements)
6
59
1
Order By: Relevance
“…Such an effect is in agreement with calculations by O'Malley [11] who used a cluster model to describe H-bond donation at site O2. Similar redistribution of spin density has been found for the phenoxyl radical in aqueous solution [14] and semiquinones [18]. When considering the spin localization on the three different sites O1+C1, O2+C2 and O3+C3, we notice a small spin transfer in going from vacuum to solution.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Such an effect is in agreement with calculations by O'Malley [11] who used a cluster model to describe H-bond donation at site O2. Similar redistribution of spin density has been found for the phenoxyl radical in aqueous solution [14] and semiquinones [18]. When considering the spin localization on the three different sites O1+C1, O2+C2 and O3+C3, we notice a small spin transfer in going from vacuum to solution.…”
Section: Methodssupporting
confidence: 81%
“…It is not clear to what extent this effect is reflected in the molecular spin density. This question has been recently addressed in an ab initio molecular dynamics (MD) study of the benzoquinone radical anion in aqueous solution [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, for smaller water shells than used here, calculations with fully converged solute-solvent clusters have been presented. 50 In Ref. 22, it has been shown that the simpler LDA can be used for the frozen part, and that it is advantageous to calculate the frozen density from a superposition of molecular densities.…”
Section: Validation Of the Solvent Modelmentioning
confidence: 99%
“…[24] These observations most likely indicate that H-bonding induces a redistribution of the electron spin density, as demonstrated earlier by Lucarini et al [26] Interestingly, the relatively large Dg iso shift of 0.0003-0.0004 between the signal of the non-hydrogen-bonded NMe2 LC (g = 2.0046) and that of NHOH LC (g = 2.0043) or NHMe LC (g = 2.0042) is consistent with the latter two radicals being H-bonded phenoxyl radicals. Indeed, theoretical [27][28][29][30] and experimental studies [6,7,[31][32][33] have indicated that hydrogen bonding to a phenoxyl (or Tyr) radical results in a considerable lowering of the g x value but leaves g y and g z essentially unaffected. Thus, assuming that g y and g z are the same for all RR' LC, a Dg x shift of 0.0012-0.0016 (3Dg iso ) is obtained.…”
mentioning
confidence: 99%